The Controversy of Indonesian Democracy Practices in The Post-Reform - Fernando, Henky; Larasati, Yuniar Galuh; Abdullah, Irwan; Ismail, Ismail; Yunani, Ahmad; Nastain , M; Morin, Leanne (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
Democracy in post-reform Indonesia does not always work, and this haseven led to controversy. However, this topic remains underexplored in scholarlydiscussions. In response to gaps in previous studies, this research focuses on thecharacteristics, factors, and controversies of post-reform democracy in Indonesia.Employing a qualitative descriptive approach rooted in case studies, this studyhighlights three key findings. First, the involvement of family members of the rulersas public officials occurs massively in high-state institutions. Second, rulersincreasingly use legal instruments to expand their political influence. Third, therulers widely practice limiting freedom of speech for citizens to maintain the statusquo. This study also recommends the importance of future studies to explaincitizens' perceptions of Indonesia's post-reform democracy by conducting intensiveinterviews. Through this process, it is expected that a more comprehensiveunderstanding of the development of democracy in post-reform Indonesia will begained.